Cultural, morphological, pathogenic and molecular diversity in Macrophomina phaseolina isolates of safflower from southern India - PRASAD*, R.D.; NAVANEETHA, T.; RAO, N. NAGESWARA (Indian Phytopathology, 2011)
Isolates of Macrophomina phaseolina that causes root rot in safflower were collected from semi arid regions ofMaharashtra (MS), Andhra Pradesh (AP) and Karnataka (K) states of India. Here we assessed the cultural, morphological,pathogenic and genetic affinity and diversity among twenty-four isolates of M. phaseolina. Principal component analysis(PCoA) of cultural and morphological parameters showed 13 groups which indicated high degree of variation among theisolates. The three major principal components considered for analysis explained 72% of the total variance. Among all thecultural characters studied variations were prominent in microsclerotia (shape, length and width) dimensions. Based onpathogenicity test of M. phaseolina isolates on susceptible safflower cultivars (cvs, ‘A1’ and NARI 6), the isolates were groupedinto three aggressiveness groups (AG) viz., low, medium and highly aggressive. The M. phaseolina isolates prevalent insafflower growing areas showed variation in their virulence and that AG3 isolates can be utilized in screening safflowergermplasm and breeding lines to identify resistance sources to Macrophomina root rot. Genetic diversity analysis usingRandom amplified polymorphic DNA (RAPD) markers and UPGMA cluster analysis distinguished the isolates into two majorgroups (Group I and Group II) and Group I has 23 isolates from safflower with a genetic similarity more than 86% among themand one isolate from castor formed a separate group with only 65% similarity Furthermore, the Group I was distinctly subdividedinto two subgroups and one subgroup has all safflower isolates from Maharashtra region showing 88% genetic similarity. Ingeneral, a moderate genetic diversity was detected despite the complexity in genetic makeup among the isolates and thismight be related to the predominant cultivation of safflower in these areas.